Pesantren without Kiai: Transforming Leadership Traditions and Boarding School Ownership - Moh. Yasin Abidin; Ta'rifin, Ahmad; Makmun Hanif; Rofiqotul Aini; Siska Rakhmawati (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
The emergence of pesantren without kiai signifies a diversification in the leadership and ownership models of pesantren in Indonesia. This study investigates the transformation of leadership and ownership in two pesantren located in Pekalongan, specifically Pondok Modern Al-Qur'an Buaran and International Muhammadiyah Boarding School (IMBS) Miftahul Ulum Pekajangan, both of which were established by non-kiai founders. Employing a qualitative-phenomenological approach, this research utilizes single-site and cross-site data analysis as modeled by Robert K. Yin. The findings indicate a transition from a traditional family-based leadership model to a more organizational structure. Furthermore, the ownership of pesantren has shifted to foundations or Islamic organizations. Consequently, the selection of pesantren caregivers is now determined by the institution or organization rather than by lineage. Nevertheless, the diverse leadership and ownership models do not reduce the interest of the community sending their children to these pesantren.